2017
DOI: 10.1097/mrr.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Robotic approaches for the rehabilitation of upper limb recovery after stroke: a systematic review and meta-analysis

Abstract: This systematic review with a meta-analysis of studies was carried out to evaluate the effectiveness of robotic training (RT) and conventional training (CT) in improving the motor recovery of paretic upper limbs in stroke patients. Numerous electronic databases were searched from January 2000 to May 2016. Finally, 13 randomized-controlled trials fulfilled the inclusion criteria and were included in the three meta-analyses. The first meta-analysis carried out for those studies using RT for stroke patients indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…Recently, Zhang et al [40] evaluated the effectiveness of robotic training and conventional training in improving the motor recovery of paretic upper limbs in stroke patients. They found significant differences in motor recovery between the conventional and robotic groups in chronic stroke patients but not in the acute/subacute stage.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhang et al [40] evaluated the effectiveness of robotic training and conventional training in improving the motor recovery of paretic upper limbs in stroke patients. They found significant differences in motor recovery between the conventional and robotic groups in chronic stroke patients but not in the acute/subacute stage.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of robotic devices on rehabilitative outcomes after stroke have been strongly investigated through randomized controlled trials (RCT) and, in the latest years, through systematic reviews and meta-analysis [29,19,28]. Robotic training can be used in addition to usual care to help both therapists and patients in the management of the paralyzed upper-limb and to achieve better rehabilitation outcomes [29].…”
Section: Effects Of Exoskeletons On Upper-limb Motor Recoverymentioning
confidence: 99%
“…The effects of robotic devices on rehabilitative outcomes after stroke have been strongly investigated through randomized controlled trials (RCT) and, in the latest years, through systematic reviews and meta-analysis [29,19,28]. Robotic training can be used in addition to usual care to help both therapists and patients in the management of the paralyzed upper-limb and to achieve better rehabilitation outcomes [29]. A recent Cochrane review, including 34 trials (1160 participants), demonstrated that stroke patients who receive electromechanical and robot-assisted arm and hand training after stroke might improve their ADL, arm and hand function and strength [19].…”
Section: Effects Of Exoskeletons On Upper-limb Motor Recoverymentioning
confidence: 99%
“…According to our knowledge of the literature, ample summary of the efficacy of various interventions for upper limb function rehabilitation in stroke patients can be found in published systematic reviews. Most of these reviews evaluate the efficacy of a single category of therapeutic technique, such as CIMT,25–29 robot-assisted therapy,30–35 bilateral training,36 37 task-oriented training,38 exercise therapy,39 functional electrical stimulation (FES),40 41 orthotics,42 43 mental practice,44 45 mirror therapy,46 47 action observation,48 non-invasive cerebral stimulation,49–52 brain-computer interface,53 54 virtual reality,42 home‐based therapy programmes55 and so on. There are also some comprehensive systematic reviews on general function treatment of upper limb after stroke56–58 or other specific problems, such as motor dysfunction,59 60 sensory impairment,61 spasticity,62 63 decreased quality of life,64 and shoulder pain and subluxation 65–67.…”
Section: Introductionmentioning
confidence: 99%